Sphaeropsidones, Phytotoxic Dimedone Methyl Ethers Produced by Diplodia cupressi: A Structure−Activity Relationship Study - Evidente, Antonio; Maddau, Lucia; Scanu, Bruno; Andolfi, Anna; Masi, Marco; Motta, Andrea; Tuzi, Angela (Journal of Natural Products, 2011)
Sphaeropsidone and episphaeropsidone are two phytotoxic dimedone methyl ethers produced by Diplodia cupressi, the causal agent of a canker disease of cypress in the Mediterranean area. In this study, eight derivatives obtained by chemical modifications and two natural analogues were assayed for phytotoxic and antifungal activities, and a structure?activity relationship was examined. Each compound was tested on nonhost plants and on five fungal pathogenic species belonging to the genus Phytophthora. The results provide insights into structure?activity relationships within these compounds. It was found that the hydroxy group at C-5, the absolute C-5 configuration, the epoxy group, and the C-2 carbonyl group appear to be structural features important in conferring biological activity. The conversion of sphaeropsidone into the corresponding 1,4-dione derivative led to a compound showing greater antifungal activity than its precursor. This finding could be useful in devising new natural fungicides for practical application in agriculture.
doi: 10.1021/np100837rdoi: 10.1021/np100837rThe following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: antifungal activity (voyant); Diplodia cupressi; Phytotoxicity; Sphaeropsidones